Substitution of concrete coarse aggregate for PET waste to manufacture cobogo (Research, Society and Development, 2022)
The current great challenge of civil construction is to be able to reduce the impacts caused by the processes, such as the generation of waste; consumption of raw materials; and the exaggerated consumption of polymers (plastics) by society. In order to reconcile these problems, this article sought to evaluate the replacement of coarse aggregate (gravel) in concrete with PET waste for the manufacture of cobogós blocks. For that, a modified concrete mixture was used as a method, where there was the total replacement of the coarse aggregate (gravel) by PET, these concretes were evaluated by means of the axial compression test at 7, 14 and 21 days. As a result, a strength of 4.07 MPa was obtained, meeting the standard for hollow concrete blocks for masonry, which in turn brings an excellent advantage in terms of sustainability.